2018
DOI: 10.1002/pen.24828
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(ether‐block‐amide)/poly(amide‐co‐poly(propylene glycol)) random copolymer blend membranes for CO2/N2 separation

Abstract: A series of poly(amide‐co‐poly(propylene glycol)) (PA‐PPG) random copolymers with different content of PPG were designed by polycondensation reaction. These random copolymers were blended up to 60% with commercially available Pebax 2533. The blend membranes were characterized by Fourier‐transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD), scanning electron microscope (SEM). Gas permeation properties of these blend membranes were investigated using five single‐gases (CO2, H2, O2, CH4, and N2) at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…On the basis of this model, the apparent activation energies for the permeation of CO 2 and N 2 are 13.8 kJ·mol −1 and 35.1 kJ·mol −1 , respectively. These results are in concordance with the reported values for Pebax ® 3533 membranes, prepared on polymeric supports, of 14.2 kJ·mol −1 for CO 2 and 29.6 kJ·mol −1 for N 2 [ 29 ] and justify the reduction in selectivity with the temperature due to the higher activation energy for N 2 with respect to CO 2 [ 42 ]. It must be taken into account that permeance is proportional to diffusion and solubility, and these two factors affect the defined apparent activation energy.…”
Section: Resultssupporting
confidence: 92%
“…On the basis of this model, the apparent activation energies for the permeation of CO 2 and N 2 are 13.8 kJ·mol −1 and 35.1 kJ·mol −1 , respectively. These results are in concordance with the reported values for Pebax ® 3533 membranes, prepared on polymeric supports, of 14.2 kJ·mol −1 for CO 2 and 29.6 kJ·mol −1 for N 2 [ 29 ] and justify the reduction in selectivity with the temperature due to the higher activation energy for N 2 with respect to CO 2 [ 42 ]. It must be taken into account that permeance is proportional to diffusion and solubility, and these two factors affect the defined apparent activation energy.…”
Section: Resultssupporting
confidence: 92%
“…Shibasaki et al reported a monodisperse poly(N-methyl benzamide) copolymerized with PPG diamine in solution to afford non-hydrogen-bondable block copolymers, which are non-crystalline materials but showing weak tensile modulus [ 35 ]. Luo et al prepared fluorene-based PA-PPG membranes via solution polycondensation with high carbon dioxide permeability [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we can attain specific and desirable characteristics that may be challenging to achieve using a single type of polymer. 5 Despite their advantages, polymer blends have limitations, which is their molecular miscibility. The properties of the blends such as molecular state of dispersion, the morphology of various phases, and the characteristics of the final products are all influenced by thermodynamics.…”
mentioning
confidence: 99%
“…25 Reijerkerk et al have reported improvement of 5 factors in CO 2 permeability (530 Barrer) on blending 1:1 ratio of PDMS/PEG polymer for CO 2 / CH 4 . 26 Zhu et al 5 investigated the blending of random copolymers of poly(amide-co-poly(propylene glycol)) (PA-PPG) with Pebax 2533. When compared to pure Pebax 2533, the Pebax/PA-PPG 50%-60% blend membrane improved CO 2 /N 2 selectivity by 68.4%.…”
mentioning
confidence: 99%
See 1 more Smart Citation